Cobalt-free layered positive electrode material and its manufacturing method, and lithium-ion battery
The cobalt-free layered positive electrode material with zinc oxide coating addresses manganese ion dissolution, improving specific capacity, initial efficiency, and cycle performance in lithium-ion batteries, offering a cost-effective manufacturing solution.
Patent Information
- Application Number
- JP2022525185
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-17
- Filing Date
- 2020-11-30
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-11-30
AI Technical Summary
Cobalt-free positive electrode materials in lithium-ion batteries face the challenge of excessive dissolution of manganese ions due to their composition, which affects the specific capacity, initial charge efficiency, and cycle performance.
A cobalt-free layered positive electrode material is developed, comprising layered lithium nickel manganate coated with zinc oxide, with a specific formula LiNi x Mn 1-x O 2 and a zinc oxide content of 0.05% to 0.3%, to prevent manganese ion dissolution in the electrolyte.
The coating effectively enhances the specific capacity, initial charge efficiency, and cycle performance of lithium-ion batteries while reducing residual alkali content, making the manufacturing method simple and cost-effective for industrial production.
Smart Images

Figure 0007617909000002 
Figure 0007617909000003 
Figure 0007617909000004
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of lithium ion battery technology, in particular to a cobalt-free layered positive electrode material for lithium ion batteries and a method for producing the same, and a lithium ion battery. [Background technology]
[0002] With the rapid development of lithium-ion power batteries, higher requirements are being placed on their cost, safety, cycle life, etc. As the core component of lithium-ion batteries, the performance of the cathode material plays an important role in the overall performance of the battery. Compared with traditional ternary cathode materials, cobalt-free cathode materials have the advantages of lower cost and more stable structure. However, since cobalt-free cathode materials do not contain cobalt and have a relatively large amount of Mn element, cobalt-free cathode materials have the problem of excessive dissolution of metallic Mn ions. Therefore, there is a need to further research into cobalt-free positive electrode materials. Summary of the Invention [Problem to be solved by the invention]
[0003] The present invention aims to at least partially solve one of the technical problems in the related art. Therefore, one of the objectives of the present invention is to provide a cobalt-free layered positive electrode material for lithium-ion batteries, in which manganese ions in the cobalt-free layered positive electrode material are not easily dissolved in an electrolyte. [Means for solving the problem]
[0004] In one aspect, the present invention provides a cobalt-free layered positive electrode material for a lithium-ion battery. According to an embodiment of the present invention, the cobalt-free layered positive electrode material includes layered lithium nickel manganese oxide in single crystal form and zinc oxide coated on the surface of the lithium nickel manganese oxide, wherein the lithium nickel manganese oxide has a general formula of LiNi x Mn 1-xO2, and 0.55≦x≦0.95. Thus, by coating the surface of the layered lithium nickel manganese oxide in a single crystal form with zinc oxide, it is possible to effectively prevent the manganese ions in the lithium nickel manganese oxide from being dissolved in the electrolyte of the lithium ion battery, and therefore it is possible to effectively improve the specific capacity, initial charge efficiency (abbreviated as initial efficiency) and cycle performance of the lithium ion battery, and the content of residual alkali (lithium hydroxide or lithium carbonate) in the cobalt-free layered positive electrode material of the present application is low.
[0005] According to an embodiment of the present invention, based on the total mass of the cobalt-free layered cathode material, the mass percentage of the zinc oxide is 0.05% to 0.3%.
[0006] According to an embodiment of the present invention, the particle size of the lithium nickel manganese oxide is 1-5 μm.
[0007] According to an embodiment of the present invention, the specific surface area of the cobalt-free layered positive electrode material is 0.1 m 2 / g~0.8m 2 / g.
[0008] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned cobalt-free layered positive electrode material. According to an embodiment of the present invention, the method for preparing the cobalt-free layered positive electrode material includes the steps of mixing a layered lithium nickel manganese oxide in a single crystal form with a zinc salt solution to obtain a mixed solution, evaporating the mixed solution to dryness to obtain a premixture, and reacting the premixture at a predetermined temperature for a predetermined time to obtain the cobalt-free layered positive electrode material. Thus, the method can coat the surface of the layered lithium nickel manganese oxide in a single crystal form with a layer of zinc oxide, effectively preventing the manganese ions in the lithium nickel manganese oxide from being dissolved in the electrolyte of the lithium ion battery, thus effectively improving the specific capacity, initial charge efficiency (abbreviated as initial efficiency) and cycle performance of the lithium ion battery, and the prepared cobalt-free layered positive electrode material has a low content of residual alkali (lithium hydroxide or lithium carbonate), and the preparation method is simple and easy to operate, convenient for industrialization, and low production cost.
[0009] According to an embodiment of the present invention, the zinc salt is selected from at least one of zinc acetate, zinc sulfate and zinc nitrate.
[0010] According to an embodiment of the present invention, the concentration of the zinc salt is 0.5-2 mol / L.
[0011] According to an embodiment of the present invention, the predetermined temperature is 400-700° C., and the predetermined time is 5-10 hours.
[0012] According to an embodiment of the present invention, the premix is reacted under an oxygen-containing atmosphere, where the concentration of oxygen is between 20% and 100%.
[0013] In yet another aspect of the present invention, there is provided a lithium ion battery, according to an embodiment of the present invention, comprising the cobalt-free layered cathode material as described above, such that the lithium ion battery has high specific capacity, high initial efficiency, and good cycle performance. [Brief description of the drawings]
[0014] The accompanying drawings, which form a part of this application, are intended to provide a further understanding of the present invention, and the illustrative embodiments of the present invention and the description thereof are intended to interpret the present invention and are not intended to unduly limit the present invention.
[0015] [Figure 1] FIG. 1 is a schematic structural diagram of a cobalt-free layered positive electrode material according to an embodiment of the present invention. [Diagram 2] 4 is a flow chart of a method for producing a cobalt-free layered cathode material according to another embodiment of the present invention. [Diagram 3] 1 is a scanning electron microscope photograph of the layered lithium nickel manganese oxide in single crystal form produced in Example 1. [Figure 4] 1 is a scanning electron microscope photograph of the cobalt-free layered positive electrode material produced in Example 1. [Diagram 5] FIG. 2 is an EDS diagram of the layered lithium nickel manganese oxide in single crystal form produced in Example 1. [Figure 6] FIG. 2 is a scanning EDS diagram of the cobalt-free layered positive electrode material produced in Example 1. [Figure 7] FIG. 2 is a diagram showing charge and discharge curves in the first week of the lithium ion battery A and the lithium ion battery B according to the first embodiment. [Figure 8] FIG. 2 is a cycle performance test chart of the lithium ion battery A and the lithium ion battery B according to the first embodiment. [Figure 9] FIG. 2 is a comparative diagram of the manganese ion contents in the electrolyte after 50 weeks of cycles for lithium ion battery A and lithium ion battery B at different temperatures according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The following examples of the present invention are described in detail. The following examples are illustrative and are intended to illustrate the present invention, and should not be construed as limiting the present invention. If specific techniques or conditions are not specified in the examples, they are in accordance with the techniques or conditions described in the literature of the relevant technical field or in accordance with the product instructions. If the manufacturer is not specified, the reagents or equipment used are all ordinary commercially available products.
[0017] In one aspect, the present invention provides a cobalt-free layered cathode material for lithium-ion batteries. According to an embodiment of the present invention, referring to FIG. 1, the cobalt-free layered cathode material 100 includes a layered lithium nickel manganese oxide 10 in a single crystal form and zinc oxide 20 coated on the surface of the lithium nickel manganese oxide, where the general formula of the lithium nickel manganese oxide 10 is LiNi x Mn 1-x O2, and 0.55≦x≦0.95. Thus, by coating the surface of the layered lithium nickel manganese oxide in a single crystal form with zinc oxide, it is possible to effectively prevent the manganese ions in the lithium nickel manganese oxide from being dissolved in the electrolyte of the lithium ion battery, and therefore it is possible to effectively improve the specific capacity, the first charge efficiency (abbreviated as the first efficiency) and the cycle performance of the lithium ion battery, and the content of the residual alkali (lithium hydroxide or lithium carbonate) of the cobalt-free layered positive electrode material of the present application is low (in some embodiments, the mass content of the residual alkali is less than 0.4%).
[0018] According to an embodiment of the present invention, based on the total mass of the cobalt-free layered cathode material, the mass percentage of zinc oxide is 0.05%-0.3%, such as 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.23%, 0.25%, 0.28%, 0.3%. Thus, the zinc oxide with the above content can well and uniformly coat the cobalt-free layered positive electrode material, so as to better prevent the manganese ions in the lithium nickel manganese oxide from being dissolved in the electrolyte; if the zinc oxide content is less than 0.05%, the coating on the lithium nickel manganese oxide will be incomplete and non-uniform, so that the content of manganese ions dissolved in the electrolyte may still be relatively high; if the zinc oxide content is more than 0.3%, because zinc oxide is an inactive material, the zinc oxide content in the cobalt-free layered positive electrode material will be large, so that the resistance of the entire layered positive electrode material will be relatively large and the specific capacity will be relatively low.
[0019] According to the embodiment of the present invention, the particle size of the lithium nickel manganese oxide is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm.Therefore, the specific capacity of the cobalt-free layered positive electrode material is relatively large, and the specific surface area is relatively small, so that the side reaction between the electrolyte and the lithium nickel manganese oxide can be further prevented, and the manganese ion can be prevented from being dissolved. If the particle size of the lithium nickel manganese oxide is less than 1 μm, the specific surface area of the lithium nickel manganese oxide is relatively large, so that the probability of the side reaction between the electrolyte and the lithium nickel manganese oxide is high. If the particle size of the lithium nickel manganese oxide is more than 5 μm, the specific capacity and the magnification performance of the cobalt-free layered positive electrode material are relatively reduced.
[0020] According to an embodiment of the present invention, the specific surface area of the cobalt-free layered positive electrode material is 0.1 m 2 / g~0.8m 2 / g, for example, 0.1m 2 / g, 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m2 / g, 0.7m 2 / g, 0.8m 2 / g. Thus, the specific surface area of the above suitable size can not only effectively ensure the good activity of the cobalt-free layered positive electrode material, but also effectively prevent the side reaction between the electrolyte and the cobalt-free layered positive electrode material, and the specific surface area of 0.1 m 2 When the specific surface area of the cobalt-free layered positive electrode material is less than 0.8 m / g, the activity of the cobalt-free layered positive electrode material is relatively small, which affects the charge / discharge performance of the lithium-ion battery. 2 Above 100 / g, there is a relatively large risk of reaction between the cobalt-free layered positive electrode material and the electrolyte, thus affecting the electrical performance of the lithium-ion battery.
[0021] In one preferred embodiment, the lithium nickel manganese oxide is LiNi 0.75 Mn 0.25 After coating the surface of the layered lithium nickel manganese oxide in single crystal form with zinc oxide, the formed cobalt-free positive electrode material has higher specific capacity, first charge / discharge efficiency, and better cycle performance.
[0022] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned cobalt-free layered positive electrode material. According to an embodiment of the present invention, referring to FIG. 2, the method for preparing the cobalt-free layered positive electrode material includes S100 to S300.
[0023] S100: A layered lithium nickel manganese oxide in single crystal form is mixed with a zinc salt solution to obtain a mixed solution.
[0024] According to an embodiment of the present invention, the step of preparing layered lithium nickel manganese oxide in single crystal form is to mix LiOH and the precursor Ni by using a high speed mixer. x Mn 1-x(OH)2 (0.50≦x≦0.95), mixing for 5 to 15 minutes at a rotation speed of 800 to 900 rpm, and reacting the mixed materials in an oxygen atmosphere (concentration of 90% or more) at a reaction temperature of 800 to 970°C (heating rate of 1 to 5°C / min) for a reaction time of 10 to 20 hours, and then naturally cooling to obtain layered lithium nickel manganese oxide in a single crystal form.
[0025] Here, in order to react the lithium nickel manganese oxide with the zinc salt uniformly, the lithium nickel manganese oxide produced by the above method is further pulverized using a crushing device to obtain powdered lithium nickel manganese oxide, which is then sieved to have 300 to 400 meshes to obtain lithium nickel manganese oxide with an appropriate particle size.
[0026] According to an embodiment of the present invention, the zinc salt is selected from at least one of zinc acetate (Zn(CH3OO)2), zinc sulfate, and zinc nitrate. This allows zinc oxide to be effectively obtained in the subsequent high-temperature reaction. Here, when zinc acetate is used, in the subsequent high-temperature reaction, zinc acetate reacts to produce carbon dioxide, water, and zinc oxide, and the zinc oxide is coated on the surface of the lithium nickel manganese oxide. When zinc sulfate is used, zinc sulfate produces zinc oxide and lithium sulfate in the high-temperature reaction (residual alkali is involved in the reaction), so that a small amount of lithium sulfate is doped into the coating layer zinc oxide at this time, which is also advantageous in reducing the content of residual alkali in the reaction. When zinc nitrate is used, zinc nitrate produces zinc oxide, nitric oxide, and / or nitrogen dioxide in the high-temperature reaction.
[0027] According to the embodiment of the present invention, the concentration of zinc salt is 0.5-2 mol / L (for example, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2.0 mol / L), which is helpful to obtain a desired content of zinc oxide. Here, the volume of the zinc salt solution can be flexibly adjusted by those skilled in the art according to the desired content of zinc oxide in the final cobalt-free layered positive electrode material, and is not limited here.
[0028] In addition, the solvent in the zinc salt solution is not particularly limited as long as it can completely dissolve the zinc salt, but can be flexibly selected by those skilled in the art according to the actual situation. For example, the solvent includes, but is not limited to, water, ethanol, etc.
[0029] S200: The mixture is evaporated to dryness to obtain a preliminary mixture.
[0030] Here, the specific method of evaporation to dryness is not particularly limited as long as it evaporates the solvent in the mixed liquid (i.e., the solvent of the zinc salt) and does not cause a reaction between lithium nickel manganese oxide and the zinc salt. For example, the mixture can be evaporated to dryness by stirring at 100°C (the temperature can be adjusted depending on the selected solvent).
[0031] S300: The premix is reacted at a predetermined temperature for a predetermined time to obtain a cobalt-free layered positive electrode material.
[0032] According to an embodiment of the present invention, the predetermined temperature is 400 to 700°C (for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C), and the predetermined time is 5 to 10 hours (for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours). This can effectively ensure the generation of zinc oxide at the above temperature. If the temperature is less than 400°C, the reaction temperature is not reached, which is unfavorable to the generation of zinc oxide, and if the temperature exceeds 700°C, the generated zinc oxide is easily diffused into the lithium nickel manganese oxide, which not only affects the activity of the lithium nickel manganese oxide, but also may cause the coating on the lithium nickel manganese oxide to be incomplete and non-uniform, which causes the dissolution of the electrolyte in the manganese ions to be relatively large.
[0033] According to an embodiment of the present invention, the premix is reacted in an oxygen-containing environment, where the concentration of oxygen is 20% to 100%. This prevents the unstable Ni in the lithium nickel manganese oxide from being dissolved in the oxygen environment. 3+ is stable Ni 2+ If the oxygen content is less than 20%, the lithium nickel manganese oxide is likely to be decomposed again, making it difficult to produce the desired product.
[0034] According to an embodiment of the present invention, after obtaining the cobalt-free layered cathode material in step S300, the method further includes a step of sieving the cobalt-free layered cathode material, the sieve mesh is 300-400 mesh, thereby obtaining the cobalt-free layered cathode material with an appropriate particle size.
[0035] According to an embodiment of the present invention, the method can coat a layer of zinc oxide on the surface of the layered lithium nickel manganese oxide in a single crystal form, effectively preventing the manganese ions in the lithium nickel manganese oxide from being dissolved in the electrolyte of the lithium ion battery, and thus effectively improving the specific capacity, first charge efficiency (abbreviated as first efficiency) and cycle performance of the lithium ion battery; and the prepared cobalt-free layered positive electrode material has a low content of residual alkali (lithium hydroxide or lithium carbonate). In addition, the preparation method is simple and easy to operate, convenient for industrialized production, and low production cost. In yet another aspect of the present invention, there is provided a lithium ion battery, according to an embodiment of the present invention, comprising the cobalt-free layered cathode material as described above, such that the lithium ion battery has high specific capacity, high initial efficiency, and excellent cycle performance.
[0036] (Example) Example 1 The method for producing the cobalt-free layered positive electrode material includes the steps of: Using a high-speed mixer, LiOH and the precursor Ni 0.75 Mn 0.25 (OH)2, mixing time is 10 minutes, rotation speed is 800 rpm, the mixed material is reacted in an oxygen atmosphere (concentration is 90% or more), reaction temperature is 930°C, reaction time is 12 hours, after the reaction is completed, the material is naturally cooled and sieved through a 400 mesh sieve to obtain layered lithium nickel manganese oxide in single crystal form; Step 2: uniformly mixing the lithium nickel manganese oxide (100 g) obtained in step 1 with an aqueous zinc acetate solution (1.2 mL) with a concentration of 1 mol / L to obtain a mixed liquid; then stirring and evaporating the mixed liquid to dryness at 100°C to obtain a premixture; and reacting the premixture at 500°C for 5 hours, in which the oxygen concentration in the reaction atmosphere is 95%; after the reaction is completed, the premixture is naturally cooled and sieved through a 400 mesh sieve to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material is 0.1% (the content of zinc ions in the cobalt-free layered positive electrode material can be measured by ICP, thereby determining the content of zinc oxide).
[0037] Analyzing the results: (1) The obtained single crystal layered lithium nickel manganese oxide and the cobalt-free layered positive electrode material were each scanned by an electron microscope. The scanning electron microscope images of the lithium nickel manganese oxide and the cobalt-free layered positive electrode material are shown in Figures 3 and 4. As is clear from Figures 3 and 4, compared with the lithium nickel manganese oxide of Figure 3, the cobalt-free layered positive electrode material of Figure 4 has a relatively rough surface and is coated with a single layer of material, and the particle size of the material does not change significantly before and after the coating.
[0038] (2) The energy spectrum (EDS) diagrams of lithium nickel manganese oxide and the cobalt-free layered positive electrode material are shown in Figures 5 and 6, respectively. As is clear from the EDS energy spectrum, the material on the surface of the cobalt-free layered positive electrode material contains zinc element, which indicates that the material coated on the surface of the lithium nickel manganese oxide is zinc oxide.
[0039] (3) The obtained lithium nickel manganese oxide and cobalt-free layered positive electrode material are dissolved in NMP with conductive agent SP and binder PVDF in a ratio of 92:4:4 and mixed uniformly to obtain a slurry. The slurry is evenly applied onto aluminum foil and dried at 100°C to obtain a positive electrode sheet. The positive electrode sheet, negative electrode (lithium sheet), electrolyte (electrolyte components are LiPF6 (lithium hexafluorophosphate) / EC (ethylene carbonate)-DMC (dimethyl carbonate)), separator, etc. are assembled into lithium ion battery A (abbreviated as battery A) and lithium ion battery B (abbreviated as battery B) in a glove box filled with argon gas. The battery model number is R2032, the separator is polypropylene microporous film (Celgard2300), and batteries A and B are similar except for the positive electrode material. Charge and discharge performance tests were conducted on lithium ion battery A and lithium ion battery B, and the results of the charge and discharge performance tests (voltage range 3.0 to 4.3 V) are shown in Figure 7 (charge and discharge curves in the first week). As can be seen in combination with Figure 7, at a discharge rate of 0.1 C, the charge and discharge specific capacities of lithium ion battery A in the first week were 201.6 mAh / g and 173.6 mAh / g, respectively, and the initial efficiency was 86.1%, while the charge and discharge specific capacities of lithium ion battery B in the first week were 201.5 mAh / g and 178.2 mAh / g, respectively, and the initial efficiency was 88.4%.
[0040] (4) The lithium-ion battery A and the lithium-ion battery B in (3) were each cycled at 1C magnification, and the cycle curves are shown in FIG. 8. As can be seen from FIG. 8, the battery capacity retention rate of the lithium-ion battery A after 50 weeks of cycling is 95%, and the battery capacity retention rate of the lithium-ion battery B after 50 weeks of cycling is 99%.
[0041] (5) The Mn ion content in the electrolyte after 50 weeks of cycles of lithium ion battery A and lithium ion battery B at different temperatures is compared, and the test results are shown in Figure 9. As can be seen from Figure 9, after being coated with zinc oxide, the amount of manganese ions in the cobalt-free layered positive electrode material dissolved in the electrolyte is greatly reduced.
[0042] Example 2 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution (volume: 1.8 mL) having a concentration of 1 mol / L, and dried and reacted under the same conditions as in Example 1 to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.15%.
[0043] Example 3 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution (volume 2.4 mL) having a concentration of 1 mol / L, and dried and reacted under the same conditions as in Example 1 to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.20%.
[0044] Example 4 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution (volume: 3.6 mL) having a concentration of 1 mol / L, and dried and reacted under the same conditions as in Example 1 to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.3%.
[0045] Example 5 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution (volume: 0.36 mL) having a concentration of 1 mol / L, and dried and reacted under the same conditions as in Example 1 to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.03%.
[0046] Example 6 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution (volume 4.8 mL) having a concentration of 1 mol / L, and dried and reacted under the same conditions as in Example 1 to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.4%.
[0047] Example 7 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution of the same concentration and volume as that of Example 1, and reacted at 400° C. for 5 hours to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.1%.
[0048] Example 8 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution of the same concentration and volume as that of Example 1, and reacted at 600°C for 5 hours to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.1%.
[0049] Example 9 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution of the same concentration and volume as that of Example 1, and reacted at 700° C. for 5 hours to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.1%.
[0050] Example 10 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution of the same concentration and volume as that of Example 1, and reacted at 300° C. for 5 hours to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.04%.
[0051] Example 11 The lithium nickel manganese oxide (100 g) obtained in Example 1 was uniformly mixed with an aqueous zinc acetate solution of the same concentration and volume as that of Example 1, and reacted at 800° C. for 5 hours to obtain a cobalt-free layered positive electrode material, in which the mass content of zinc oxide in the cobalt-free layered positive electrode material was 0.1%.
[0052] Example 12 Step 1: Mix LiOH and Ni precursor together using a high-speed mixer. 0.55Mn 0.45 The same as in Example 1 except that (OH)2 was mixed, and the layered lithium nickel manganese oxide LiNi 0.55 Mn 0.45 Get O2.
[0053] Step 2 is the same as in Example 1.
[0054] (Example 13) Step 1: Mix LiOH and Ni precursor together using a high-speed mixer. 0.95 Mn 0.05 The same as in Example 1 except that (OH)2 was mixed, and the layered lithium nickel manganese oxide LiNi 0.95 Mn 0.05 Get O2.
[0055] Step 2 is the same as in Example 1.
[0056] Comparative Example 1 Same as step 1 of Example 1, but without coating.
[0057] Comparative Example 2 Step 1: Mix LiOH and Ni precursor together using a high-speed mixer. 0.45 Mn 0.55 (OH)2, the mixing time is 20 minutes, the rotation speed is 700 rpm, the mixture is reacted in an oxygen atmosphere (concentration is 80%), the reaction temperature is 1000°C, the reaction time is 24 hours, and after the reaction, it is naturally cooled and sieved through a 400 mesh sieve to obtain layered lithium nickel manganese oxide in the form of a single crystal.
[0058] Step 2: The lithium nickel manganese oxide (100g) obtained in step 1 is uniformly mixed with a zinc acetate aqueous solution (48mL) having a concentration of 0.1mol / L to obtain a mixed liquid; then, the mixed liquid obtained is stirred and evaporated to dryness at 100°C to obtain a pre-mixture; then, the pre-mixture is reacted at 300°C for 15 hours, where the oxygen concentration in the reaction atmosphere is 15%; after the reaction, the mixture is naturally cooled and sieved through a 400 mesh sieve to obtain a cobalt-free layered positive electrode material, where the zinc oxide content in the cobalt-free layered positive electrode material is 0.4% (the zinc oxide content can be determined by measuring the zinc ion content in the cobalt-free layered positive electrode material by ICP).
[0059] Comparative Example 3 Step 1: Mix LiOH and Ni precursor together using a high-speed mixer. 0.75 Mn 0.15 Co 0.10 The same as in Example 1 except that (OH)2 was mixed, and the layered lithium nickel manganese oxide LiNi 0.75 Mn 0.15 Co 0.10 Get O2.
[0060] Step 2 is the same as in Example 1.
[0061] The same method and conditions as in Example 1 were used to combine the cobalt-free layered positive electrode materials obtained in Examples 2 to 13 and Comparative Examples 1 to 3 into lithium ion batteries, and the specific capacity of the first week of charge and discharge of the batteries was tested at a discharge rate of 0.1C, the cycle performance of the batteries (50-week cycle) was tested at a rate of 1C, and the content of manganese ions in the electrolyte of the batteries was tested at 50°C (the test conditions were all the same as in Example 1). The test results are shown in Table 1.
[0062] [Table 1]
[0063] As can be seen from Examples 1 to 6, when the content of zinc oxide is within the range of 0.05% to 0.3%, the discharge specific capacity of the lithium ion battery is high, the cycle capacity retention rate is also relatively high, and the content of manganese ions dissolved in the electrolyte after 50 weeks of cycles is also relatively low. When the content of zinc oxide is low, the content of manganese ions dissolved in the electrolyte is relatively high (coating on lithium nickel manganese oxide is incomplete), and therefore the discharge specific capacity and cycle capacity retention rate of the lithium ion battery are reduced. When the content of zinc oxide is high, the discharge specific capacity of the lithium ion battery is reduced, and the content of zinc oxide coated on the surface of lithium nickel manganese oxide is relatively high, which further improves the structural stability of the cobalt-free layered positive electrode material and reduces the dissolution of manganese ions, and therefore the cycle capacity retention rate of the battery can be relatively improved. Considering the overall performance of the lithium ion battery, the present application limits the content of zinc oxide to the range of 0.05% to 0.3%, so that the lithium ion battery has good overall performance.
[0064] As can be seen from Examples 1 and 7 to 11, the content of zinc oxide in the cobalt-free layered positive electrode material was consistent (except Example 10), but as the reaction temperature increased, zinc oxide gradually dispersed from the surface of the lithium nickel manganese oxide into the lithium nickel manganese oxide. The higher the temperature, the higher the content of zinc oxide dispersed in the lithium nickel manganese oxide and the lower the content of zinc oxide distributed on the surface. Therefore, when the reaction temperature is less than 400°C (for example, Example 10), the content of the generated zinc oxide is low, which causes the surface coating of the lithium nickel manganese oxide to be incomplete, and the content of manganese dissolved in the electrolyte to be relatively high, thus reducing the discharge specific capacity and cycle performance of the lithium ion battery. When the reaction temperature exceeds 700°C (for example, Example 11), a lot of zinc oxide diffuses into the lithium nickel manganese oxide, which causes the amount of manganese ions dissolved in the electrolyte to be relatively high, thereby reducing the discharge specific capacity of the lithium ion battery. Therefore, in consideration of the good overall performance of the lithium ion battery, the present application limits the reaction temperature to within the range of 400°C to 700°C.
[0065] In the present specification, a description that refers to terms such as "one embodiment," "some embodiments," "examples," "specific examples," or "several examples" means that the specific features, structures, materials, or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In the present specification, general expressions for the above terms do not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials, or characteristics described can be combined in any suitable manner in any one or more embodiments or examples. Furthermore, a person skilled in the art can make combinations and combinations of different embodiments or examples and features of different embodiments or examples described in the present specification without mutual contradiction.
[0066] Although the embodiments of the present invention have been shown and described above, the above embodiments are illustrative and should not be understood as limiting the present invention, and it should be understood that those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. 1. A cobalt-free layered positive electrode material for a lithium ion battery, comprising: The present invention includes a layered lithium nickel manganese oxide having a single crystal form and zinc oxide coated on the surface of the lithium nickel manganese oxide, wherein the lithium nickel manganese oxide has a general formula of LiNi0.75Mn0.25O 2 and Based on the total mass of the cobalt-free layered cathode material, the mass percentage of the zinc oxide is 0.1% to 0.3%; A cobalt-free layered positive electrode material for lithium-ion batteries, comprising:
2. The particle size of the lithium nickel manganese oxide is 1 to 5 μm.
2. The cobalt-free layered positive electrode material of claim 1 .
3. The specific surface area of the cobalt-free layered positive electrode material is 0.1 m 2 / g to 0.8m 2 / g, 2. The cobalt-free layered positive electrode material of claim 1 .
4. A method for producing the cobalt-free layered cathode material according to any one of claims 1 to 3, comprising the steps of: Mixing the layered lithium nickel manganese oxide in single crystal form with a zinc salt solution to obtain a mixed solution; evaporating the mixture to dryness to obtain a premix; reacting the pre-mixture at a predetermined temperature for a predetermined time to obtain the cobalt-free layered cathode material. A method comprising:
5. The zinc salt is selected from at least one of zinc acetate, zinc sulfate, and zinc nitrate.
5. The method of claim 4.
6. The concentration of the zinc salt is 0.5 to 2 mol / L; 5. The method of claim 4.
7. The predetermined temperature is 400 to 700°C, and the predetermined time is 5 to 10 hours.
5. The method of claim 4.
8. The premix is reacted under an oxygen-containing atmosphere, wherein the concentration of oxygen is between 20% and 100%.
5. The method of claim 4.
9. 1. A lithium ion battery, The cobalt-free layered positive electrode material according to any one of claims 1 to 3, A lithium-ion battery characterized by:
Citation Information
Patent Citations
Manufacture of positive electrode active material for lithium secondary battery
JP1996171910A
Lithium nickel composite oxide, manufacture thereof, and positive electrode active substance for secondary battery
JP1998069910A
Electrode active material for lithium secondary batteries, method for manufacturing the same, and lithium secondary battery containing the same
JP2005510017A
Particulate electrode material having a coating made of a crystalline inorganic material and / or an inorganic-organic hybrid polymer, and method for producing the same
JP2016504711A
Cathode active material for secondary battery, manufacturing method therefor, and lithium secondary battery comprising same
WO2019235885A1